The Effect of Green Supply Chain Management on Business Performance and Competitiveness in Malang SMEs - Alwin Gibral; Fien Zulfikarijah; Kenny Roz Firdaus (Jamanika (Jurnal Manajemen Bisnis dan Kewirausahaan), 2022)
The purpose of this study was to determine the effect of green supply chain management on business performance and competitiveness in the chips SME industry in Malang city. This type of research uses explanatory research with a quantitative approach. The number of samples used 72 respondents. Respondents in this study are business owners who have operated for more than 2 years. The source of data in this study was obtained from the distribution of questionnaires (primary data). The data analysis technique used Structural Equation Model (SEM) based on Partial Least Square (PLS). The results show that green supply chain management has a significant positive effect on SME business performance and SME competitiveness. Competitiveness has a significant positive effect on SME business performance, and green supply chain management has a significant positive effect on business performance mediated by the SMEs competitiveness.